Temperature-Responsive Self-Assembly Nanochaperone Protects Green Fluorescent Proteins from Thermal Denaturation - Shuyue Zhao; Bingqiang Li; Yiqing Song; Shian Wu; Haodong Hu; Jianzu Wang; Linqi Shi; Fan Huang (Supramolecular Materials)
Protein products perform important roles in the biochemistry field, but the thermal inactivation of proteins will increase the difficulty of their transport, storage and application. Therefore, improving the thermal stability of proteins has become a thorny challenge. Natural molecular chaperones can efficiently improve the resistance of proteins to environmental stimuli by reversible supramolecular assembly with proteins. Inspired by this machine, herein we designed a nanochaperone (nChap) with thermo-responsive amphiphilic surfaces that can prevent thermal denaturation and facilitate refolding of green fluorescent proteins (GFPs). By mimicking the hydrophobic microregion of natural chaperones, this nChap can effectively capture free GFPs and hide them into surface confined spaces, thereby shielding exposed hydrophobic sites of GFPs and preventing their irreversible thermal aggregation. When the heat stimulation disappeared, the thermosensitive segments of the nChaps underwent the hydrophilic transition, which provided suitable microenvironments for GFPs refolding. More importantly, nChaps could also actively adsorb to the surface of immobilized GFPs at high temperatures and realize the satisfactory dissociation of the nChap-protein complex upon cooling, which exhibited excellent chaperone-like activity. This work provides significant insights for understanding and developing strategies to improve protein stability.